The Female Hagiographic Profile of Vita Patrum: : The Case of Monegund of Tours - Prata da Costa, Juliana (Revista Melibea, 2023)
The aim of this article is to present a discussion of the female hagiographic profile present in the Liber Vitae Patrum of Gregory of Tours. Among the characters privileged by the hagiographer in the compilation of lives, being abbots, monks and bishops, the main categories present in the set, we note the presence of a single wo- man: Monegunda, the recluse. In this sense, it seems significant to discuss the as- pects listed by the author as preponderant in the delimitation of the profile of saint elaborated in the Vita Patrum.